2019
DOI: 10.1007/s11239-019-01937-3
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of anticoagulant therapy in atrial fibrillation at discharge from a geriatric ward: cross sectional study

Abstract: Oral anticoagulants (OACs) are effective in preventing stroke in older people with atrial fibrillation (AF), but they are often underused in this particularly high-risk population. The aim of the study was to identify health and functional determinants of oral anticoagulant therapy (OA) in AF at discharge from a geriatric sub-acute ward. A cross-sectional study was conducted and patients who presented with atrial fibrillation were analyzed. They were interviewed, examined, assessed with comprehensive geriatric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
(32 reference statements)
1
8
0
Order By: Relevance
“…Overall, these findings demonstrate that those variables which discourage the use of OAC in elderly hospitalized patients (severe functional dependence and/or frailty status, anemia, and nursing-home discharge) are also strongly associated with an increased short-term mortality in these patients [1,3,4,6]. Moreover, mortality in individuals not prescribed OAC is markedly higher than in those receiving OAC therapy, and not accounted for by an excess of thrombo-embolic fatal events, but rather reflecting the higher proportion of oldest old with complex comorbidities and poor health status in the untreated population [9].…”
Section: To the Editormentioning
confidence: 68%
See 1 more Smart Citation
“…Overall, these findings demonstrate that those variables which discourage the use of OAC in elderly hospitalized patients (severe functional dependence and/or frailty status, anemia, and nursing-home discharge) are also strongly associated with an increased short-term mortality in these patients [1,3,4,6]. Moreover, mortality in individuals not prescribed OAC is markedly higher than in those receiving OAC therapy, and not accounted for by an excess of thrombo-embolic fatal events, but rather reflecting the higher proportion of oldest old with complex comorbidities and poor health status in the untreated population [9].…”
Section: To the Editormentioning
confidence: 68%
“…We read with great interest the study by Wojszel et al including 95 patients with atrial fibrillation (AF) admitted to a geriatric sub-acute ward [1]. The Authors concluded that in the real-life population of patients with AF comprehensive geriatric assessment (CGA) might allow to increase significantly the number of patients on oral anticoagulants (OACs), but this is limited by patient's anemia diagnosis and frailty status, this latter assessed according to the deficit accumulation model proposed by Rockwood et al [2].…”
Section: To the Editormentioning
confidence: 99%
“…Noninvasive methods of diagnosis include a stress test, rest and stress ECG, SPECT (single-photon emission tomography), PET (positron emission tomography), magnetic resonance, and cardiac computed tomography [ 25 , 44 ]. The limited physical capacity or frailty syndrome limits the possibility of performing stress tests in patients with AF, and the stress test results are mostly inconclusive [ 37 , 45 , 46 , 47 , 48 ]. These contribute to referrals for invasive diagnostics, exposing patients to potential risks [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decision to conduct cardiac catheterization after noninvasive test results indicate a high risk of significant coronary vessel changes improves the effectiveness of coronary angiography [ 14 , 20 ]. However, stress testing before the intervention is significantly less often performed in the older age group, and older patients less often show objective signs of ischemia [ 40 ].The traditional stress test is often inconclusive in AF, and the frailty of patients with AF is an additional obstacle that limits the possibility of performing stress tests [ 38 , 41 ]. Because of the possibility of triggering an episode of AF, dobutamine stress ECHO is not considered as the primary alternative [ 42 ].…”
Section: Discussionmentioning
confidence: 99%